TAMTSIL AL-HUWIYYAH WA AT-TAHMISY FI SYI’R AS-SALAMU ’ALAIKUM LI ANIS CHOUCHÈNE - Dzurrotul Qomariyah; Nur Hasaniyah; Ummi Hasanah (Journal of Arabic Literature (JaLi), 2024)
This study aims to analyze the representation of identity and marginalization in Anis Susan’s poem "As-salaam ‘alaikum" using Charles Sanders Peirce’s semiotic theory. Adopting a qualitative approach with content analysis, this study examines symbols and meanings that reflect identity and marginalization. The poem is the primary data source, while secondary sources include academic references on identity, marginalization, and Peirce’s semiotics. Data collection involves document analysis and identifying words, phrases, and sentences as symbolic elements. These symbols are categorized into three types: (1) Identity Symbols, representing cultural, religious, and ethnic aspects; (2) Marginalization Symbols, highlighting social discrimination and oppression; and (3) Social Criticism Symbols, addressing systemic or ideological issues. The study applies Peirce’s triadic model, analyzing the representamen (symbolic form), object (referenced concept), and interpretant (derived meaning). Findings reveal that the poem employs linguistic and semiotic symbols to reflect a collective identity deeply rooted in cultural and social contexts. Identity is expressed through religious and cultural references, while marginalization appears in language structures conveying victimization and protest. The poem also critiques social injustice through poetic imagery, emphasizing oppression within the existing system